Diploid aposporous sunflower forms triploid BIII progeny displaying increased apospory levels and non-random genetic mutations - Silvina Pessino; Graciela Nestares; Marta B. Bianchi; Iara Katzaroff; Lucía Amato; Marika Bocchini; Gianpiero Marconi; Emidio Albertini; Ana C. Ochogavía (Scientific Reports)
Abstract Apomixis (asexual reproduction via seeds) has the potential to revolutionize sunflower breeding. In previous studies, we identified a diploid sunflower line (Rf975) that naturally exhibits extra gametophytes resembling aposporous apomictic embryo sacs (AES). Here, we investigated the nature (reduced vs. unreduced) and viability of these AES-like gametophytes by examining the formation of triploid (3x) BIII hybrids (2n + n) in the progeny of Rf975. Flow cytometry analysis of immature seeds revealed that, on average, 42.8% of self-pollinated Rf975 progeny were triploids, although only 36.6% of them reached maturity. Cytoembryological analysis showed that 100% of triploids exhibited some degree of apospory, with an average expressivity of 61.9%. Abnormal pollen grains and limited viable seeds were also noted. A segregant F2 progeny, comprising diploid and triploid individuals, was generated by crossing Rf975 with HA89, a genetically divergent sexual diploid. SNP-based progeny tests discarded that diploid Rf975 forms clonal matroclinal progeny at levels greater than 18%. Furthermore, specific non-random genetic and DNA methylation changes were detected in the F2 triploids compared to F2 diploids and parental plants, highlighting recurrent (epi)genetic alterations occurring during triploidization. This research could contribute to the future implementation of apomixis-based strategies in sunflower breeding.